Alpha-tocopherol: An alternative solution for the adverse effects of dental bleaching on dentin adhesion - Albaricci, Maria Carolina da Costa [UNESP]; Marcomini, Natália [UNESP]; Costa, Joatan Lucas de Sousa Gomes; Barros, Antonia Patricia Oliveira [UNESP]; Galvani, Lucas David [UNESP]; Kuga, Milton Carlos [UNESP]; Dantas, Andréa Abi Rached [UNESP] (Elsevier, 2024)
Purpose: This study evaluated the effect of solutions of different concentrations of alpha-tocopherol on hybrid layer formation and microtensile bond strength of endodontically treated teeth bleached with 38% hydrogen peroxide. Materials and methods: Sixty bovine incisors were randomly distributed into six groups (n = 10). In the control group (CONT), no intervention was performed. In the 38HP group, only bleaching with 38% hydrogen peroxide was conducted. In the 15AT, 20AT, 25AT, and 10SA groups, bleaching with 38% hydrogen peroxide was followed by the application of alpha-tocopherol at 15%, 20%, 25%, or 10% sodium ascorbate, respectively. Subsequently, bond strength was performed using the microtensile test, and the formation of the hybrid layer was examined through scanning electron microscopy. The obtained data were subjected to Kruskal-Wallis and Dunn tests (α = 0.05). Results: For bond strength, groups CONT and 20AT displayed higher values compared to HP. There were no significant differences in the other groups compared to the control. 38HP, 10SA, 20AT and 25AT exhibited a predominance of adhesive failures, while CONT and 15AT presented more cohesive failures in dentin. In the evaluation of the hybrid layer, the CONT group showed greater formation of longer resin tags than 38HP and 15AT, which presented a predominance of few and short resin tags (p < 0.05). Conclusion: Alpha-tocopherol at 20% is capable of minimizing the deleterious effects of dental bleaching on the hybrid layer formation and bond strength to dentin.
Keywords: Alpha-tocopherol; Antioxidant; Dental bleaching; Hydrogen peroxide; Polymerization